2023
DOI: 10.1007/s00125-023-05974-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted serum proteomics of longitudinal samples from newly diagnosed youth with type 1 diabetes distinguishes markers of disease and C-peptide trajectory

Abstract: Aims/hypothesis There is a growing need for markers that could help indicate the decline in beta cell function and recognise the need and efficacy of intervention in type 1 diabetes. Measurements of suitably selected serum markers could potentially provide a non-invasive and easily applicable solution to this challenge. Accordingly, we evaluated a broad panel of proteins previously associated with type 1 diabetes in serum from newly diagnosed individuals during the first year from diagnosis. To u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Eleven of the 81 significant biomarkers were higher, and 70 were lower in the T1D cohort compared with Healthy . Cytokines with notable associations to the pathogenesis or prevention of type 1 diabetes included C-type lectin domain family 4 member D (CLEC4D, p<0.0001),13 interleukin (IL)-4 (p<0.0001),14 IL-1215 (p<0.05), IL-1316 (p<0.05), galectin-1 (Gal-1, p<0.0001),17 tumor necrosis factor superfamily member 14 (TNFSF14, p<0.0001),18 islet cell antigen 1 (ICA1, p<0.0001),19 CD40 ligand20 (p<0.05), mannan-binding lectin-associated serine proteases (MASP-1, p<0.0001),21 peroxiredoxin-1 (PRDX1, p<0.01),22 and latency-associated protein transforming growth factor beta 1 (LAP-TGF-beta 1, p<0.001) 23. (figure 4)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the 81 significant biomarkers were higher, and 70 were lower in the T1D cohort compared with Healthy . Cytokines with notable associations to the pathogenesis or prevention of type 1 diabetes included C-type lectin domain family 4 member D (CLEC4D, p<0.0001),13 interleukin (IL)-4 (p<0.0001),14 IL-1215 (p<0.05), IL-1316 (p<0.05), galectin-1 (Gal-1, p<0.0001),17 tumor necrosis factor superfamily member 14 (TNFSF14, p<0.0001),18 islet cell antigen 1 (ICA1, p<0.0001),19 CD40 ligand20 (p<0.05), mannan-binding lectin-associated serine proteases (MASP-1, p<0.0001),21 peroxiredoxin-1 (PRDX1, p<0.01),22 and latency-associated protein transforming growth factor beta 1 (LAP-TGF-beta 1, p<0.001) 23. (figure 4)…”
Section: Resultsmentioning
confidence: 99%
“…13 PRDX1 22 is an antioxidant with immunoregulatory properties that were lower in T1D. LAP-TGF-beta 1 23 is the upstream pro-protein of immunoregulator TGFbeta 1 and was lower in T1D. Notably, TGF-beta 1 dissociates from LAP and becomes active on interaction with primarily integrin ITGAV:ITGB6 32 and can promote Th17 or Treg differentiation in a concentration-dependent manner.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…The proteomics study 34 found 12 significant associations between peptide expression changes in the initial 12 months after diagnosis and C-peptide glucose ratio slopes, with expression changes in GPX3 being indicative of future C-peptide changes. Because of the cohort and methodological differences, a direct comparison is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent single-omics papers have been published on the INNODIA cohort 34,35 with a considerable overlap of patients to our study. There are small differences in the inclusion criteria of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A review has shown that the high IGF-1 concentrations can prevent or delay the inception of diabetes-related complications in people with diabetes ( 5 ). According to a targeted serum proteomics study, lower levels of IGF1 and IGFBP3 and elevated IGFBP1 level were detected in the sera of T1D youth ( 6 ). There were additionally studies confirmed that adiponectin and INSR were crucial in regulating glucose metabolism and insulin sensitivity ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%